PERAN PEMERINTAH DALAM PEMBERIAN BANTUAN HUKUM BAGI MASYARAKAT DALAM PROSES PEMBERIAN UANG GANTI RUGI PENGADAAN TANAH DI IBU KOTA NUSANTARA (IKN) YANG DITITIP DI PENGADILAN (KONSINYIASI) - Andri Pranata; Tajuddin (JOURNAL OF LAW AND NATION, 2024)
One of the decisions that is quite phenomenal in Indonesia at the moment is when the Government of the Republic of Indonesia decided to move the State Capital from Jakarta to East Kalimantan. The move of the capital city is expected to level development and reduce the pressure of population density and moving the capital city is also considered a step to increase resilience. against natural disasters. Jakarta is vulnerable to flooding and land shrinkage, while the new location in East Kalimantan is considered safer from these risks. Apart from that, moving the capital city is considered an opportunity to build new infrastructure and spur economic growth in the region. Meanwhile, the reason for those who refuse is that moving the capital city is a large project that requires significant financial investment and human resources. The land acquisition process will never be separated from the issue of compensation, so research needs to be carried out first on all information and data submitted in making an estimate of compensation. If an agreement has been reached regarding the form and amount of compensation, then payment of compensation will be made and then continued with the release or transfer of rights to the land concerned. In principle, the government in this case should provide facilities to the community concerned in providing legal aid services to deal with judicial process in receiving compensation money entrusted, because morally the government in this case has the responsibility to provide legal protection for its people. Don't just take the land and then leave it to solve its own problems. Moreover, the government actually has many components that can be used to provide legal aid services. This research is normative legal research. Currently, the role of the Regional Government in providing legal assistance to the community in the process of providing compensation money for land acquisition in the Indonesian Capital City (IKN) which is entrusted to the court (consignment) does not yet exist and in efforts to provide legal assistance to the community those affected are: Complicated administrative processes and incomplete documents often become obstacles, Social and Communication Problems due to lack of socialization and education to the community regarding their rights and land acquisition procedures causing misunderstanding and conflict, Legal processes in court that take time and money become a burden on society. Apart from that, limited access to legal aid institutions or experienced advocates is also a major obstacle.